Développement humain, développement durable et « pays en développement » : comment articuler et mesurer les différentes dimensions ? - Bruno Boidin (Développement Durable et Territoires)
This article seeks to specify the place of various dimensions of sustainable development within development economics, in particular human and social dimensions. This leads us to consider the complex relations between the various assets (health, education, social capital…), characterized by irreversibility effects which can jeopardize sustainability. It is therefore necessary to find a measure of sustainable development, taking into account these interactions between dimensions. We propose criteria to evaluate synthetic measurements of sustainable development, and apply them to selected indicators.